(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
As harmony with modernized environmental developments which were appeared within economical , banking areas with what accompanied of chances or challenges , the matter is required to face those modernizations , adaptation with them , as considering them strength points not weak points , and these developments banking marketing as it should be on the Iraqi public banks and private and hybrid to take advantage of this process to increase excellence and the expansion of the banking business opportunities, , enlarge in the banking businesses especially the banking transaction are distinguished by serious competition & strong between banks , and the final result is to serve Iraqi banking system & customers that the national economy targets it. The research aims to highlight on concept of banking marketing , its significance in many of fields , in addition to its importance to fulfill the competitive distinction of the banks between each other , or others of aims , the research has made group of conclusions and recommendations.